Agri Produce Management An option for alleviating rural poverty - Mohapatra, Suchismita; Mahapatra, C R; Sahu, Gayatri (Indian Farming, 2021)
With a majority of its population (83.3 cr) living in villages, poverty is a major problem in rural India. Most of the people from rural areas pursue agriculture and allied activities. But lately, they are quitting farming and improper management of agri produce is one of the major causes. Due to the lack of efficient infrastructure and food processing industry about 30- 35 % of all foods produced in India are wasted. Farmers face problems such as lack of adequate and scientific storage, inadequate knowledge and facilities for processing, faulty marketing system, strict government policies for contract farming, etc. These problems can be managed through various management practices discussed under the topic.